Application of drill bit coatings for fiber/metal stack drilling in aircraft manufacturing: a comprehensive review - Joy Mathavan, J. (The International Journal of Advanced Manufacturing Technology, 2025)
The integration of hybrid composite/metal stack panels in aircraft manufacturing introduces significant advancements by combining the strengths of both materials. This review paper examines the critical role of coated drill bits in addressing the challenges associated with drilling these advanced materials. Coatings, such as Ti-based and diamond coatings, are shown to enhance drill bit performance by increasing wear resistance, reducing friction, and improving heat management. These improvements lead to better drilling outcomes, including reduced temperatures, minimized delamination, lower burr forma tion, and superior surface roughness and circularity. The review highlights the effectiveness of various coatings and their impact on drilling parameters like thrust force and torque, while also addressing the complexities of managing wear and maintaining diameter consistency. Ultimately, the strategic use of drill bit coatings and careful optimization of drilling con ditions are essential for achieving high-quality results and advancing efficiency and sustainability in aircraft manufacturing.
Keywords: Aerospace engineering; Drill bit; Tungsten carbide; Microscopic characterization and microanalysis; Wear